Relational continuity of oral health care in Indigenous communities: a qualitative study - Richa Shrivastava; Yves Couturier; Stefanik Simard-Lebel; Felix Girard; Nadia Verenna Bendezu Aguirre; Jill Torrie; Elham Emami (BMC, 2019)
Abstract Background The relational continuity of care is an essential function of primary health care. This study reports on the perspectives of Cree communities and their primary health care providers regarding the barriers and enablers of relational continuity of oral health care integrated at a primary health care organization. Methods A multiple case study design within a qualitative approach and developmental evaluation methodology were used to conduct this research study in Cree communities of Northern Québec. Maximum variation sampling and snowball techniques were used to recruit the participants. Data collection consisted of individual interviews and focus group discussions. Thematic analysis was conducted which included transcription, debriefing, codification, data display, and interpretation. The consolidated criteria for reporting qualitative studies (COREQ) were used to guide the reporting of study findings. Results A total of six focus group discussions and 36 individual interviews were conducted. Five major themes emerged from the thematic analyses for barriers (two) and enablers (three). Themes for barriers included impermanence and lack of effective communication, whereas themes for enablers included culturally competent professionals, working across professional boundaries, and proactive organizational engagement. Conclusions Based on these findings, relational continuity can be empowered by effective strategies for overcoming barriers and encouraging enablers, such as recruitment of permanent professionals, organizing cultural competency training, development of a Cree language dental glossary, encouraging inter-professional collaboration, and promoting the organization's efforts.